Datura Stramonium Leaf Extract Mediated Co3O4@ZnO, Co3O4@NiO, and Co3O4@CuO Core-Shell Nanostructures: Investigation of their Anticancer, Antibacterial, and Antioxidant Activities - Gezahegn Tadesse (ASTU, 2024)
Investigating potent anticancer, antibacterial, and antioxidant core-shell nanostructures (CSNs) using the green method is highly preferred as it is an environmentally friendly approach. In this work, Co3O4@ZnO (CZ), Co3O4@NiO (CN), and Co3O4@CuO (CC) CSNs, as well as Co3O4, ZnO, NiO, and CuO metal oxide nanoparticles (MONPs) were synthesized employing D. stramonium leaf extract. The XRD confirmed the formation of the cubic Co3O4, hexagonal wurtzite ZnO, face-centered cubic NiO, and monoclinic CuO MONPs, as well as cubic hexagonal CZ, cubic-face-centered cubic CN, and cubic-monoclinic CC CSNs. The average crystallite size of Co3O4(11), ZnO(11), NiO(11), and CuO(11) MONPs was found to be 11, 17, 12, and 13 nm, whereas CZ(11), CN(11), and CC(11) CSNs were 22, 13, and 15 nm, respectively. The diffraction peaks of the core and shell were slightly shifted, which suggests the formation of core-shell nanostructures. The spherical CZ, prismatic CN, and cylindrical CC CSNs with particle sizes of 21.1, 16.99, and 11.07 nm were revealed from TEM analysis, respectively. Additionally, the HR-TEM image reveals a less-contrast shell enclosing a dark core, and lattice fringes are found in both regions. The polycrystalline nature of CZ, CN, and CC CSNs was also revealed from SAED analysis. The in vitro cytotoxicity of CZ, CN, and CC CSNs and the Epirubicin drug against MCF-7 cancer cells at 800 μg/mL were found to be 95.22, 81.38, 97.72, and 96.15%, whereas against PBMC they were 66.44, 51.94, 62.43, and 65.18%, respectively. The CC CSNs showed stronger anticancer activity even than the Epirubicin drug with less cytotoxicity. The IC50 of CZ, CN, and CC CSNs was revealed to be about 18.3, 21.25, and 17.8%, respectively. The in vitro antibacterial activity of Co3O4(11), ZnO(11), NiO(11), and CuO(11) NPs against S. aureus showed IC50 values of 22.22, 18.36, 28.55, and 17.21 μg/mL and against E. coli were 33.3, 27, 36, and 26 μg/mL, respectively. The low IC50 of CuO(11) NPs indicates the high inhibition activity of CuO NPs in contrast to the other. CZ, CN, and CC CSNs showed IC50s of 11.6, 23.46, and 14 μg/mL against S. aureus, but 17.55, 26, and 21.76 μg/mL against E. coli, respectively. The percentage scavenging activity of Co3O4, ZnO, NiO, and CuO NPs and CZ, CN, and CC CSNs against DPPH radical at 500 μg/mL were 63.308, 75.385, 57.0769, 74.872, 86.87, 65.98, and 76.32%, respectively. As a result, CSNs exhibit stronger antibacterial and antioxidant activity than corresponding individual MONPs due to basic features and synergistic effects within the core-shell structure.
Keywords: Antibacterial, Anticancer, Antioxidant, Core-shell, Datura stramonium